2018
DOI: 10.13181/mji.v27i3.2156
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between urinary albumin to creatinine ratio and systemic glycocalyx degradation in pediatric sepsis

Abstract: Background: Increased capillary permeability in sepsis is associated with several complications and worse outcomes. Glycocalyx degradation, marked by increased serum syndecan-1 levels, alters vascular permeability, which can manifest as albuminuria in the glomerulus. Therefore, elevated urinary albumin to creatinine ratio (ACR) potentially provides an index of systemic glycocalyx degradation. The aim of this study was to analyze the correlation between urinary ACR and serum syndecan-1 levels.Methods: A longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A study by Saragih et al reported that the average syndecan-1 level in healthy children was 27.7ng/mL, with a level of > 41.42ng/mL (90 th percentile) indicating marked glycocalyx degradation. ( 25 ) This suggests that syndecan-1 was increased for all pediatric sepsis subjects enrolled in this study. This is in line with several studies in adults, which reported increased levels of glycocalyx components such as syndecan-1 and hyaluronan during sepsis.…”
Section: Discussionmentioning
confidence: 71%
“…A study by Saragih et al reported that the average syndecan-1 level in healthy children was 27.7ng/mL, with a level of > 41.42ng/mL (90 th percentile) indicating marked glycocalyx degradation. ( 25 ) This suggests that syndecan-1 was increased for all pediatric sepsis subjects enrolled in this study. This is in line with several studies in adults, which reported increased levels of glycocalyx components such as syndecan-1 and hyaluronan during sepsis.…”
Section: Discussionmentioning
confidence: 71%
“…This condition leads to capillary The results of this study showed that pediatric patients with sepsis had the highest median syndecan-1 level of 2.92 (0.06 -83.00) ng/mL in the baseline measurement, slightly decreased, and continued to increase up to 2.55 (0.05 -52.40) ng/mL at the 48th-hour observation. Previous research at the pediatric ICU (PICU) Cipto Mangunkusumo Hospital, Indonesia, showed that the level of syndecan-1 in pediatric sepsis was 83.40 (10.10 -2257.91) ng/mL compared to the controls 27.7 ng/mL and that this value increased in the first three days and began to decline on the seventh day (20). Another research on the adult population at an intensive care unit (ICU) in Sweden showed that the median level of syndecan-1 in septic shock patients was 246 (180 -496) ng/mL compared to controls 26 (23 -31) ng/mL, which were not correlated with mortality (21).…”
Section: Discussionmentioning
confidence: 97%
“…Glycocalyx damage can range from discrete disturbances in the composition of the entire luminal layer to excessive destruction and degradation, with the loss of the entire glycocalyx. Furthermore, the difference in glycocalyx thickness, basal turnover, speed, and degradation severity can affect this marker's level (20).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies revealed that the mean urine ACR was 10.5 (3-88) mg/g, and the mean syndecan-1 level was 27.7 (SD 2.24) ng/mL (19).…”
Section: Thismentioning
confidence: 92%